Spiritual Emotional Freedom Technique (SEFT) Analysis of the Anxiety Levels of Primigravida Pregnant Women in the Third Trimester - Hidayat, Asri (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Background:When facing childbirth, anxiety about giving birth often occurs. Anxiety that is not resolved properly causes changes in the function of the autonomic nervous system/ANS, worsens cardiovascular adaptation and risks complications in pregnant women.Purpose:This research aims to identifySpiritual Emotional Freedom Technique(SEFT) Regarding the Anxiety Level of Primigravid Pregnant Women in the Third Trimester.Methods:Qualitative study with a case study approach. The informants in this study consisted of 10 primigravida pregnant women who were recruited through purposive sampling. Data collection through in-depth interviews using data collection instruments, in-depth interview guides, field notes, audio recorder. By analyzing data using Collezi thematic analysis.Results:The results of the qualitative analysis showed that two major themes were studiedSpiritual Emotional Freedom Technique(SEFT) Regarding the Anxiety Level of Primigravida Pregnant Women in the Third Trimester, namely; 1) Spiritual Emotional Freedom Technique (SEFT) process, 2) Spiritual Emotional Freedom Technique (SEFT) results.Conclusion:Spiritual Emotional Freedom Technique(SEFT) is good for women who are undergoing pregnancy to reduce feelings of anxiety and worry, especially the worries experienced by pregnant women in the third trimester, the feelings of anxiety and worry are increasing. Pregnant women feel the benefits of SEFT. They feel the effectiveness of SEFT and can continue to practice SEFT in a sustainable manner.